Pelaksanaan Posyandu di Masa Adaptasi Kebiasaan Baru (Studi Kualitatif) - Yudi Adnan (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Health service activities such as posyandu must still be carried out by implementing health protocols. Puskesmas must continue to encourage posyandu to be active in health services for infants and toddlers. Objective: This study aims to evaluate the input, process and output of the implementation of the toddler or immunization services at the posyandu. Method: This type of the study was a qualitative with purposive sampling of informants. There were 10 (ten) informants representing Lurah Malili, Babinsa, Kader Posyandu, parents of toddlers or caregivers, midwife, puskesmas officers and community leaders. The data collection technique used in-depth interview techniques with descriptive analysis. This research was carried out in one of the Posyandu for toddlers, Malili Village, Malili District, East Luwu Regency, South Sulawesi Province in August and September 2021. Results: The results showed that the implementation of Posyandu in Malili Village in terms of personnel, funds, facilities and infrastructure, implementation of Health protocols and number of visits was in good category and carried out in accordance with applicable guidelines. Conclusion: Puskesmas Malili needs to evaluate its performance and programs every year. In addition, increasing the facilities and funds needed at the posyandu.